Peran Media Sosial dalam Mendorong Inovasi Rasa, Bentuk, dan Persepsi Kekinian Jajanan Indonesia di Era Digital: Studi Literatur - Muhammad Aulia Moeslim; M. Alfito Dwian; Fatma Tresno Ingtyas; Laurena Ginting (Garina, 2025)
This study aims to analyze the role of social media in driving innovation in flavor, shape/appearance, and modern perception of Indonesian traditional snacks in the digital era through a literature review from 2020–2025. Social media functions not only as a promotional tool but also as a creative and collaborative space that influences how traditional snacks are created, modified, and perceived. The findings indicate that social media accelerates the spread of new flavor trends and encourages the exploration of modern tastes without abandoning cultural identity. In addition, visual aesthetics on social media inspire innovation in the shape and presentation of snacks to make them more appealing and easily viral. Social media also shapes modern perceptions through cultural storytelling that rebrands traditional snacks as contemporary, relevant, and culturally valuable. However, challenges arise from the limited digital and branding skills among MSME actors. Overall, social media serves as a catalyst for the synergy of flavor, visual, and cultural innovation, bridging tradition and modernity in the development of local culinary products.